Diachrony as an encumbrance - Nejedlý, Petr (Bohemica Olomucensia, 2018)
If linguists investigate history and development of lexical units, they only rarely use the diachronic method to analyse a word "without any history" - a forgery. They endeavour to prove forgery of those words this way because these expressions correspond to such development neither by their form, nor by their contents. Sometimes, such investigation arrives at conclusions which combine both language development and hypothetical genesis of the forgery. This is questionable, for any result of a single individual linguistic creativity of a forger is not possible to deduce from regularities of a continuous development proven at words recorded objectively in a period of time of existence of a national language. Searching for the origin of the noun varyto, recorded in the Rukopis královédvorský [Dvůr Králové manuscript], can illustrate the whole matter satisfactorily. Linguistics usually presupposes or even claims that the forgers found inspiration in Greek barbitos. Such connection could have perhaps been deduced if a Czech expression did exist as a word which had its undoubted past, however, in case of a forged expression we miss sufficiently sound arguments. We can find a variant explanation in language of the society of the Czech National Revival directly.
Keywords: development of the lexical unit; diachronic method; reconstruction of the etymon; Dvůr Králové manuscript; varyto